Pengaruh Eco-Enzyme dan Air Kelapa Pada Tanaman Sawi Samhong King (Brassica rapa subsp chinensis L.) Pada Sistem Hidroponik di Seameo Biotrop Bogor - Maulida, Siti; Syah, Bastaman; Rianti, Winda (JURNAL AGROPLASMA, 2025)
Eco-enzyme is a process that can be used to valorize organic waste (fresh vegetable, fruit peel waste), in which fermentation is added brown sugar and water and selective microorganisms are used, namely bacteria and yeast. In addition to enzymes that can help plant growth and development, there are also hormones that are involved and interact with enzymes. Plant metabolic rate. One of the plants that require enzymes and hormones in its growth and development is the Brassicaceae family, namely samhong mustard greens. This research was conducted at the SEAMEO BIOTROP greenhouse located at Jalan Raya Tajur Km 6, Pakuan, South Bogor Sub-district, Bogor City, West Java, Indonesia. The research was conducted from April 2022 to May 2022. The research method used is the experimental method, employing a Double Factor Randomized Block Design (RBD) with treatments consisting of eco-enzyme factor with 4 levels: b0 (AB mix (control)), b1 (EE 8 ml/L), b2 (EE 10 ml/L), and b3 (EE 12 ml/L) and coconut water factor with 3 levels: k1 (2 ml/L), k2 (4 ml/L) and k3 (6 ml/L). Observation data were analyzed by analysis of variance and further tested by Duncan's multiple range test at the 5% level. The results of the F test and DMRT test showed that the treatment combination b0ke (AB mix and coconut water 6 ml/L) gave the best results on all observation parameters (plant height, number of leaves, root length, and plant fresh weight). Keywords: AB Mix, coconut water, eco enzyme, samhong king